RESPONSIBILITY OF PUBLIC SERVICE IN HANDLING CUSTOMER COMPLAINTS OF THE MUARA TIRTA REGIONAL PUBLIC DRINKING WATER COMPANY IN GORONTALO CITY - Fidriansyah, Kemal; Igirisa , Irawaty; Tui, Fenty Prihatini Dance (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2025)
This study aims to evaluate the responsiveness of public services in handling customer complaints at the Muara Tirta Regional Drinking Water Company (Perumdam) in Gorontalo City. The sub-focus of this study is 1). Ability to respond to customers. 2) Speed ​​of service. 3) Accuracy of service. 4) Accuracy of service. 5) Timeliness of service. 6) Ability to respond to customer complaints. The method used is a qualitative approach, primary data obtained through in-depth interviews conducted with various informants including the Director, Customer Relations Manager, Assistant Manager of Subscription Services & Marketing and Assistant Manager of Distribution Transmission and Disturbances, customers, secondary data from journal books. Data analysis was carried out through the stages of classification, reduction, description and drawing conclusions. The results of the study indicate that 1) Perumdam Muara Tirta’s ability to respond to customer complaints is not yet consistent. Because even though communication channels and efforts by officers are available, there are still delays in handling. 2) The speed of service at Perumdam Muara Tirta is still inconsistent, where simple complaints can be handled quickly but complex cases often exceed the target, so it is necessary to improve coordination and optimize SOPs so that services are more consistent with customer expectations. 3) the accuracy of service at Perumdam Muara Tirta still varies, because there are customers who get solutions according to complaints, but some others still experience recurring problems. 4) the accuracy of service at Perumdam Muara Tirta has received attention through the implementation of SOPs and field verification, but its implementation in the field still needs to be strengthened so that each customer complaint can be handled more carefully, precisely and completely. 5) the timeliness of complaint services at Perumdam Muara Tirta, Gorontalo City, in general has been attempted through picket schedules, standby teams and the implementation of SOPs, but in the field some customers have not fully experienced the service according to the promised time. 6) The ability to respond to customer complaints at Perumdam Muara Tirta has been demonstrated through rapid response efforts and information transparency, however, technical limitations and field constraints mean that the benefits of these services have not been fully felt equally by all customers. Perumdam Muara Tirta must strengthen the consistency of SOP implementation, improve coordination between departments, strengthen the capacity and accuracy of officers in handling complaints, and increase transparency and accountability of information to customers.